2017
DOI: 10.1002/eat.22802
|View full text |Cite
|
Sign up to set email alerts
|

Normal white matter microstructure in women long‐term recovered from anorexia nervosa: A diffusion tensor imaging study

Abstract: Objectives: Studies point to white matter (WM) microstructure alterations in both adolescent and adult patients with anorexia nervosa (AN). These include reduced fractional anisotropy in several WM fiber tracts, suggesting reduced WM integrity. The extent to which these alterations are reversible with recovery from AN is unclear. There is a paucity of research investigating the presence of WM microstructure alterations in recovered AN patients, and results are inconsistent. This study aimed to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
0
13
1
Order By: Relevance
“…It has been demonstrated that it does not merely coincide with an increase in weight: cognitive impairments and psychopathological signatures, such as obsessive thoughts and body image concerns may persist (Steinhausen, ; Zipfel et al, ). In our review, four articles out of six showed no difference in FA between recovered AN and HC (Bang, Ro, & Enderstad, ; Miles, Kaplan, French, & Voineskos, ; Pfuhl et al, ; Yau et al, ). Zhang et al (), too, showed no differences between weight‐restored AN patients and HC.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…It has been demonstrated that it does not merely coincide with an increase in weight: cognitive impairments and psychopathological signatures, such as obsessive thoughts and body image concerns may persist (Steinhausen, ; Zipfel et al, ). In our review, four articles out of six showed no difference in FA between recovered AN and HC (Bang, Ro, & Enderstad, ; Miles, Kaplan, French, & Voineskos, ; Pfuhl et al, ; Yau et al, ). Zhang et al (), too, showed no differences between weight‐restored AN patients and HC.…”
Section: Resultsmentioning
confidence: 64%
“…Although most of the studies focused on acutely ill patients, some of them involved patients who had recovered from AN, in order to determine whether the DTI findings reflected state or trait characteristics of the disorder. These studies used comparable samples in terms of age and BMI and, while one of them showed the presence of some FA alterations in recovered AN patients compared to HC (Shott et al, ), the other ones showed no between‐group differences (Bang et al, ; Pfuhl et al, ; Yau et al, ; Zhang et al, ). Interestingly, these results are in line with the findings of other studies that investigated WM volumes by means of different methodological approaches (i.e., VBM; Seitz et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in recovered AN patients have reported no differences in DWI parameters (Bang, Rø, & Endestad, 2018;Yau et al, 2013). The current study assessed individuals with a diagnosis of AN based on DSM-IV criteria, with the exception of the amenorrhea criterion.…”
Section: Discussionmentioning
confidence: 86%
“…Most studies report lower FA in widespread WM regions, including the corpus callosum (CC) (Frieling et al, 2012;Frank et al, 2013;Shott et al, 2016;Gaudio et al, 2017;Phillipou et al, 2018;von Schwanenflug et al, 2019), fornix fibers (Kazlouski et al, 2011;Frank et al, 2013;Gaudio et al, 2017), thalamus (Frieling et al, 2012;Hu et al, 2017), cingulum (Kazlouski et al, 2011;Frank et al, 2013), posterior thalamic radiation (PTR) (Phillipou et al, 2018), superior longitudinal fasciculus (SLF) (Via et al, 2014), fronto-occipital fasciculus (FOF) (Kazlouski et al, 2011;Via et al, 2014), corona radiation (Shott et al, 2016;Phillipou et al, 2018) and cerebellum (Nagahara et al, 2014;Shott et al, 2016). Five studies, however, observed no significant FA differences between AN patients and HC (Yau et al, 2013;Cha et al, 2016;Pfuhl et al, 2016;Bang et al, 2018;Olivo and Swenne, 2019). Two studies also reported higher FA in corona radiation, SLF, FOF, PTR, and CC (Frank et al, 2013;Vogel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%